Ethics of Regional Autonomy With Local Wisdom - Fauzi, Sudar; Sumarna, Andri; Haryono, Merda Budi; Hanapia, Cepi; Rahmawati (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
Regional autonomy is a strategic instrument for building and empowering local communities in order to achieve equitable, civilised and humane economic development. This concept is synonymous with public services, so its implementation must be based on ethics. Ethics, including bureaucratic ethics, have a dual function: as a guideline for public bureaucracy in exercising its authority so that actions taken are considered good and commendable, and as a standard for evaluating bureaucratic behaviour that reflects integrity and professionalism. In this context, local wisdom is an important foundation because it contains noble values born from the life experiences of the local community, such as mutual cooperation, mutual assistance, diversity, and good character. These values have been a hallmark of Indonesian civilisation since the era of the archipelago's kingdoms until today. This study aims to examine the concept of regional autonomy ethics based on the local wisdom of the Indonesian people, with Pancasila as the highest moral guideline and philosophy of life. The study uses a qualitative method with a descriptive literature review approach, analysing relevant literature on the relationship between government ethics, regional autonomy, and local wisdom values. The findings indicate that integrating bureaucratic ethics with local wisdom can strengthen the legitimacy of regional policies, enhance public participation, and promote the creation of a clean, transparent, and public service-oriented governance system. The implications of this research underscore the need for the formulation of regional autonomy policies that consistently accommodate local cultural and moral values for sustainable development.